Analysis of the Relationship Between Labor Force Size and BPJS Ketenagakerjaan Participation: A Case Study of North Sumatra Province (Nomico, 2026)
Labor force growth is one of the important indicators in observing the dynamics of employment in a region. However, an increase in the labor force is not always accompanied by an increase in participation in social security programs, particularly Social Security Administrator for Employment (BPJS Ketenagakerjaan). This study aims to analyze the relationship between the labor force and the level of participation in Social Security Administrator for Employment (BPJS Employment) in North Sumatra Province from August 2022 to February 2025. The study uses a quantitative method with a correlational approach, utilizing official data from the Central Statistics Agency (BPS) and Satu Data Ministry of Manpower. The analysis was conducted using manual calculations and SPSS software through Pearson's correlation test. The results of the study show a correlation coefficient value of 0.3927, indicating a moderate positive relationship between labor force growth and an increase in the number of BPJS Ketenagakerjaan participants. These findings show that although an increase in the labor force tends to be followed by an increase in the number of BPJS Ketenagakerjaan participants, other factors beyond the size of the labor force also play a role in shaping participation rates, such as the composition of formal and informal workers, economic dynamics, labor policies, and the level of corporate compliance. This study emphasizes the importance of a more targeted strategy in increasing the coverage of employment social security so that it can cover all workers, especially informal sector workers, who are dominant in North Sumatra.